Simulation of the Foreground-Background Queue in Parallel Systems - Sousa, Alexandre Magno de; Murta, Cristina Duarte (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2010)
This paper presents a simulation study of the FB scheduling policy in the presence of system loads of varying intensity and variability. The FB policy is compared with the policies FCFS, PS and SRPT, under the same conditions, in mono and multiprocessor environments. The results show that the policy FB is very appropriate for extreme situations, in which there is large variability in service time workload and high load intensity.